Typification, morphological characterization and distribution of Knautia gussonei (Caprifoliaceae) - Bartolucci, Fabrizio; Conti, Fabio (Phytotaxa, 2014)
Knautia gussonei is a species endemic to central Italy, described by Szabó and was based on a herbarium specimen collected by Gussone in Abruzzo. This species was long neglected or misinterpreted by Italian botanists and confused with K. drymeia subsp. centrifrons. Accordingly, to correct the application of this name, a specimen collected by Gussone in Abruzzo and kept in NAP is designated here as the lectotype. For K. gussonei a detailed morphological description and information about habitat, phenology and distribution are provided. Furthermore, morphological comparison between K. gussonei and K. drymeia subsp. centrifrons is provided.